The effect of a one-leg cycling aerobic training program during the rehabilitation period in soccer players with anterior cruciate ligament reconstruction - Olivier, N.; Weissland, T.; Legrand, R.; Berthoin, S.; Rogez, J.; Thevenon, A.; Prieur, F. (Clinical Journal of Sport Medicine, 2010)
The article presents a randomized clinical trial on the changes in the muscle oxygenation and cardiorespiratory fitness of soccer players who underwent the anterior cruciate ligament reconstruction. It examines the effect of the one-leg cycling (OLC) aerobic training program executed on the rehabilitation period. It mentions that 24 male soccer players were distributed randomly to one of two groups. Moreover, the result manifests that OLC training appears to end the effects of hypoactivity.